Perancangan Human Resource Scorecard untuk Mengevaluasi Kinerja Divisi Rekrutmen XYZ Group - Erwin, Marten; Wibisono, Eric; Hadiyat, Mochammad Arbi (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract— XYZ Group has been expanding their bussiness in various sector i.e., retail, IT consultants, food & beverages, shopping plazas, Japanese restaurants, e-wallets, e-commerce, and expeditions. XYZ Group continues to expand as an action to survive and win the competition. Therefore, XYZ Group’s Recruitment Division plays an important role in business activities. The Human Resource Scorecard is an appropriate method for measuring performance in XYZ Group's recruitment division. The result of Human Resource Scorecard in the XYZ Group Recruitment Division are acquiring 17 Key Performance Indicators (KPI) consisting of financial perspective two KPIs, three customer perspective KPIs, eight operational perspective KPIs, and four strategic perspective KPIs. Performance measurement is carried out by weighting process, followed by performance measurement based on the required data. The measurement results show an overall performance of XYZ’s Recruitment Division is 3,534, which means the performance of the XYZ Group’s Recruitment Division is good. Financial perspective performance gets a value of 2.5 (good enough), customer perspective performance gets a value of 3,831 (good), operational perspective performance gets a value of 3,423 (good), and strategic perspective performance gets a value of 4 (good). Based on the KPI that didn’t reach the target, an action plan was made. In addition to the action plan, performance dashboard and analysis of cause and effect relationships after measurement have been made. Keywords: human resource scorecard, key performance indicator, performance dashboard Abstrak— XYZ Group telah melakukan ekspansi di berbagai bidang, yaitu retail, grocery, IT consultant, food & beverages, shopping plaza, Japanese restaurant, e-wallet, e-commerce, dan ekspedisi. XYZ Group terus melakukan ekspansi sebagai tindakan untuk bertahan dan memenangkan persaingan. Oleh karena itu, Divisi Rekrutmen XYZ Group memegang peranan penting dalam aktivitas bisnis. Human Resource Scorecard menjadi metode yang sesuai untuk melakukan pengukuran kinerja pada divisi rekrutmen XYZ Group. Perancangan Human Resource Scorecard pada Divisi Rekrutmen XYZ Group menghasilkan 17 Key Performance Indicator (KPI), yaitu dua KPI perspektif financial, tiga KPI perspektif customer, delapan KPI perspektif operational, dan empat KPI perspektif strategic. Pengukuran kinerja dilakukan dengan melakukan pembobotan dilanjutkan pengukuran kinerja berdasarkan data yang diperlukan. Hasil pengukuran menunjukkan kinerja keseluruhan sebesar 3,534 yang berarti kinerja Divisi Rekrutmen XYZ Group tergolong baik. Kinerja perspektif financial mendapatkan nilai sebesar 2,5 (cukup baik), kinerja perspektf customer sebesar 3,831 (baik), kinerja perspektif operational sebesar 3,423 (baik), dan kinerja perspektif strategic sebesar 4 (baik). Berdasarkan KPI yang tidak mencapai target dibuat action plan. Selain action plan, dilakukan perncangan performance dashboard dan analisis cause and effect relationship setelah pengukuran. Kata kunci: human resource scorecard, key performance indicator, performance dashboard